SISTEM PANAS BUMI DAERAH KALAWAT, KABUPATEN MINAHASA UTARA, PROVINSI SULAWESI UTARA - Yamin, Riza Asyari; Patonah, Aton; Hardiyono, Adi; Hadi, Muhammad Nur (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Kalwat Geothermal Field administratively is located in North Minahasa District, North Sulawesi Province. Litologies of this research area divided by pyroclastic flows and lava. The heat source of this location comes from Mahawu Mountain that located in the southwest outside the research area. Lithology which acts as the cap rock layer is form by pyroclastic flow that has clay minerals which impermeable. Based on petrographic and PIMA abalysis, the alteration minerals that arise are dominated bu montmorillonite and halloysite, so the alteration type of this research area is argilic type and located at the northwest and southwest of research area. The water type that appears are dilute chloride-bicarbonate type and bicarbonate type. Based on the calculation of paleotemperature and geothermometer, there is increase of temperature during the form of mineral and the recent temperature. This is due to increased of volcanic activity in the research area. This research area is water-dominated and moderate temperature system that has range of temperature at 209-2100 C.